Manfaat Yoga untuk Mengurangi Nyeri Haid pada Remaja Putri di SMA Islam Al-Falah Kota Jambi - Sri Maharani; Fatihatul Hayati (Jurnal Abdimas Kesehatan (JAK), 2022)
Dysmenorrhea is pain during menstruation caused by uterine muscle spasms. The cause of dysmenorrhea is due to increased levels of prostaglandins. This increase will result in uterine contractions and vasoconstriction of blood vessels. The blood flow to the uterus decreases so that the uterus does not get a adequate supply of oxen which causes pain intensity pain influenced by the individual's description of the pain or the perception of pain experience. Treatment efforts to reduce dysmenorrhea are by administering pharmacological therapies such as analgetic drugs, hormonal therapy therapy with non-steroidal anti-prostaglandin drugs and cervical canal dilatation. Yoga is a technique that teaches such as relaxation techniques, breathing, and body position to increase strength, balance and reduce pain. External targets The results of educational activities on the benefits of yoga to reduce menstrual pain will be published in the form of a national scientific journal so that it can be accessed by the public. This community service activity was held at Al-Falah Islamic High School in Jambi City. Implementation time in January 2021. The target in this activity is students of grade X and XI of Sma Islam Al-Falah Jambi City. The result is that students understand the benefits of yoga to reduce menstrual pain. It is recommended that students more often follow activities that provide knowledge for students by attending other health counseling so as to increase the knowledge of adolescents.